Doping in Contest-Like Situations - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
Individuals who compete in a contest-like situation (for example, in sports, in promotion tournaments, or in an appointment contest) may have an incentive to illegally utilize resources in order to improve their relative positions. We analyze such doping within a tournament game between two heterogeneous players. Three major e.ects are identified which determine a player's doping decision — a cost e.ect, a likelihood e.ect and a windfall-profit e.ect. Moreover, we discuss whether the favorite or the underdog is more likely to be doped, the impact of doping on overall performance, the influence of increased heterogeneity on doping, the welfare implications of doping, and possible prevention of doping.
Keywords: K42; J3; M5; 330; contest; doping; drugs; fraud in research; tournament